1978
DOI: 10.1017/s0016672300018474
|View full text |Cite
|
Sign up to set email alerts
|

Digynic triploidy in rabbit blastocysts after delayed insemination

Abstract: The origin of triploid (3N) 5j-day blastocysts in rabbits is inferred from the segregation of sex chromosomes and of an autosomal M-marker whose properties are described. 39 triploids and no tetraploids were scored among 1454 chromosomally scored blastocysts. A delay of 8 h between an ovulatory injection and subsequent insemination raised the estimated normal incidence of 0-59 % triploid blastocysts to 3-13 %. The increase is ascribed primarily to digyny (17 blastocysts), and to diandry probably mediated by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…and XY,/? (Fechhcimer and Beatty, 1974;Beatty and Coulter, 1978). Six male calico cats had complements of XX/XXY (four) and XY/XXY (two) (Centcrwall and Benirschke, 1973).…”
Section: Diploid-triploid Chimeras In Other Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…and XY,/? (Fechhcimer and Beatty, 1974;Beatty and Coulter, 1978). Six male calico cats had complements of XX/XXY (four) and XY/XXY (two) (Centcrwall and Benirschke, 1973).…”
Section: Diploid-triploid Chimeras In Other Mammalsmentioning
confidence: 99%
“…Of the total of 43. none was XX/XYY. Two of the rabbit embryos (Beatty and Coulter, 1978) were from parents bearing different Cband autosomal markers. It was established that the triploid cell line of both was digynic; both cell lines of both embryos contained a single paternal genome.…”
Section: Diploid-triploid Chimeras In Other Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…No opportunity was afforded to examine genetic markers in the present case. There may be species differences involved as studies such as that of Beatty and Coulter (1978) in rabbits showed that the majority of triploids were due to digyny. These, however, were induced triploids due to delayed insemination.…”
Section: Discussionmentioning
confidence: 99%